AN ANALYSIS OF RELATED FACTORS WITH NURSE’S MOTIVATION IN DOCUMENTATION OF NURSING CARE IN SICKROOM OF MADANI PALU GENERAL HOSPITALS - Metrys Ndama; Aminuddin Aminuddin (Jurnal Kesehatan Prima, 2017)
Abstract : An increasing of customer’s awareness and an emphasis of health service outcomes.  Patients increasingly demand for health care providers including nurses in order to provide professional services. Nursing documentation is a proof of professional nursing services. Professional accoutabilty and responsibilty is one of the important reasons to make accurate documentation. The nurse must make an accurate and complete medical record concerning nursing care which given to the client. The Nurse’s motivation is one of the factors that encourages someone to do somehing including carrying out nursing documentation. The research objective was to nalyze the factors associated with the nurse’s motivation in documentation of nursing care in Sickrooms of Madani Palu General Hopital. The research method utilized analytical with crossectional study disign. The population was 56 nurses who officiate in Sickrooms of Madani General Hospital. The sample was 56 nurses, and the data was collected by questionnaire. The data analysis utilized univariate and bivariate alaysis with Chi Square test. The research finding was obtained there was no significant correlation among education level (p = 1.00), Gender (p = 1.00), length on work (p = 0.34), employment status (p = 0.86), Hospital regulation (p = 0.96), work conditions (p = 0.07) with nurse’s motivation in documentation of nursing care (Ho accepted). Whereas supervision variable (p = 0.005) and rewards (p = 0.000) meant that there was significant correlation among supervision and reward variables with nurse’s motivation in documentation of nursing care (Ho was rejected). It can be concluded that variables which has a significant correlation with nurse’s motivation in recording of nursing care are supervison and reward. It is suggested to the Management of Madani General Hospital to improve documentation of complete nursing cares is required a regular supervison to the nurses and also provide an appropriate rewards for them who carry out documentation properly.